PENGARUH STATUS GIZI KURANG PADA PENDERITA TERHADAP KEGAGALAN PENGOBATAN TUBERKULOSIS PARU DI B.P.4 SEMARANG - Anna Theresia Regina Ritonga; Winarto -; M. Sulchan (Universitas Muhammadiyah Semarang, 2005)
Introduction. l'r/HO predicted that there would be 591.000 new Tuberculosis cases in 2001. Tuberculosis is the second leading cause ofdeath out of t3 leading causes in Indonesia. Nutritional status, social economic condition, and level at education play vital role to cure Tuberculosis. Objective: to find out correlation between patient' nutrientdeficiencis and the failure to cure pulmonary Tuberculosis.Methods. The design was a Case Contro[ Sutty, with pTB (Pulmonary Tuberculosis) patientsfrom 8.P.4 Semarangfrom 1998 to 2000 as sample with a total ofihtrty -five patient as cases and forty - seven patient as control. Data were collected include patient weight, height, age,-sex, marital status, level of education and income.. Result. There was no significant dffirence in witght at the biginntng . of treatment between cases and control ( p:0,1 ), but there was a significant difference in ieight at the end if